A Systematic Review and Meta-analysis on Omentoplasty for the Management of Abdominoperineal Defects in Patients Treated for Cancer. Issue 4 (April 2020) - Blok, Robin D.; Hagemans, Jan A. W.; Klaver, Charlotte E. L.; Hellinga, Joke; van Etten, Boudewijn; Burger, Jacobus W. A.; Verhoef, Cornelis; Hompes, Roel; Bemelman, Wilhelmus A.; Tanis, Pieter J.
Abstract : Objective: The objective of this systematic review and meta-analysis was to examine the effects of omentoplasty on pelviperineal morbidity following abdominoperineal resection (APR) in patients with cancer. Background: Recent studies have questioned the use of omentoplasty for the prevention of perineal wound complications. Methods: A systematic review of published literature since 2000 on the use of omentoplasty during APR for cancer was undertaken. The authors were requested to share their source patient data. Meta-analyses were conducted using a random-effects model. Results: Fourteen studies comprising 1894 patients (n = 839 omentoplasty) were included. The majority had APR for rectal cancer (87%). Omentoplasty was not significantly associated with the risk of presacral abscess formation in the overall population (RR 1.11; 95% CI 0.79–1.56), nor in planned subgroup analysis (n = 758) of APR with primary perineal closure for nonlocally advanced rectal cancer (RR 1.06; 95% CI 0.68–1.64). No overall differences were found for complicated perineal wound healing within 30 days (RR 1.30; 95% CI 0.92–1.82), chronic perineal sinus (RR 1.08; 95% CI 0.53–2.20), and pelviperineal complication necessitating reoperation (RR 1.06; 95% CI 0.80–1.42) as well. An increased risk of developing a perineal hernia was found for patients submitted to omentoplasty (RR 1.85; 95% CI 1.26–2.72). Complications related to the omentoplasty were reported in 4.6% (95% CI 2.5%–8.6%). Conclusions: This meta-analysis revealed no beneficial effect of omentoplasty on presacral abscess formation and perineal wound healing after APR, while it increases the likelihood of developing a perineal hernia. These findings do not support the routine use of omentoplasty in APR for cancer. Abstract : Supplemental Digital Content is available in the text